ANALISIS PENGARUH SISTEM INFORMASI MANAJEMEN BERBASIS KOMPUTER, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PEMERINTAHAN PROVINSI DKI JAKARTA - Sutiyadi, Sutiyadi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The aim of this paper is to examine the effects of management information system, training and discipline on employees performance at government sector in Jakarta. The questionnaires were administeredto get primary data from 60 persons. Descriptive statistics and path analysis were used to explain the variance in outcome variables. The result shows that there is a significant influence of the variables of management information system, training and work dicipline toward the work performance among the employees, either partially or simultaneously. Partially, variable of management information system indicates the highest influence toward employees performance with R2 = 0,312. Meanwhile, simultaneously the three independent variables determine the highest influence toward variable of work performance with adjusted R2 = 0,469. Keywords: management information system, training, discipline, employees performance